Axisymmetric evaluation of analytic potentials around thin disks. Issue 4 (15th December 2015) - Carlson, W. B.; Carlson, K. L.
ABSTRACT: Axisymmetric potential fields among disk conductors are an important consideration for evaluation and testing of near field electric field gradients in electrical systems. As contrasted with numerical methods, analytical methods give exact solutions via the fundamental symmetry, and, in addition, we can compare the solutions to the accuracy of the test procedure. Analysis and superposition of the disk potentials is a valuable way to study the optimal characteristics of the fringing fields in dielectric systems. Cylindrical and ellipsoidal coordinate based analytical approaches are provided for the determination of the theoretical potentials in disk electrode systems.